WOMEN’S PLANNING DECISIONS AND CHOICES AFFECT FINANCIAL WELLNESS IN LATER LIFE - Hounsell, C (Innov Aging, 2018)
Longevity comes with risks as well as decisions and choices. A short-term financial outlook adds to the risk and creates additional challenges that affect the elderly, their children and their families. Today’s seniors are spending more time in retirement than in the years planning for it. There is a need to reframe the discussion as too many people are at risk for running out of money. Women’s longer life expectancies have not led them to take a long-term view. The subject of retirement causes women great concern because of their lower lifetime earnings and time out of the workforce for caregiving. The likelihood of being single with reduced income and increasing health care needs will also present major financial problems in retirement for women. This session will explore recent research on women’s financial security needs and the gaps in their income as they age. Panelists will present research on retirees 85 and over and how they are managing their finances, on how residents in the U.S., U.K., and Australia are (or are not) preparing for their retirement, as well as on the barriers to savings that exist for Latina workers. Finally, the session will discuss the policy implications of these findings for improving women’s long-term financial security.